All before them : student opportunities and nationally competitive fellowships - McCray, Suzanne, 1956-; Cutchins, Doug (University of Arkansas Press, 2015)
Advisors face quite a challenge as they sort through the daunting and ever-changing world of nationally competitive undergraduate and graduate fellowships in order to assist talented students searching for funding for exceptional academic opportunities. This collection of essays helps advisors by providing information about major changes in the fellowship and scholarship landscape. Included is guidance on the new Schwarzman scholarship for study in China, the recently added video interview for the Mitchell scholarship, and the new rules for the Rhodes personal statement (an advisor's take). Additionally, seasoned advisors share practical advice, ranging from workshops that engage students and faculty to helpful technological tools to personal statements and office assessments. Keeping the focus on the scholar in the scholarship process is a central theme. All before Them is an important addition to any faculty mentor's or scholarship advisor's toolkit.